Learning‐Challenged Youth Show an Abnormal Relationship Between Fronto‐Parietal Myelination and Mathematical Ability. Issue 5 (13th June 2020) - Denyer, Ronan; Morris, Sarah R.; Greeley, Brian; Ferris, Jennifer K.; White, Katherine; Laule, Cornelia; Boyd, Lara A.; Weber, Rachel C.
ABSTRACT: BACKGROUND AND PURPOSE: Differences in the microstructure of fronto‐parietal white matter tracts have been associated with mathematical achievement. However, much of the supporting evidence relies on nonspecific diffusion‐weighted magnetic resonance imaging, making it difficult to isolate the role of myelin in math ability. METHODS: We used myelin water imaging to measure brain myelin. We related myelin water fraction (MWF) to Woodcock‐Johnson III (WJ‐III) basic math scores using region of interest (ROI) and tract‐based spatial statistics (TBSS) analyses, in 14 typically developing and 36 learning challenged youth aged 9‐17 years. RESULTS: The ROI analysis found a positive relationship between fronto‐parietal MWF and math in typically developing youth, but not in learning challenged youth. The relationship between fronto‐parietal MWF and math observed in typically developing youth was fully mediated by age. No group differences in fronto‐parietal MWF were found between typically developing and learning challenged youth. TBSS also found no group differences in MWF values. TBSS indicated math‐MWF relationships extend beyond fronto‐parietal tracts to descending and ascending projection tracts in typically developing youth. TBSS identified math‐MWF relationships in the cerebral peduncles of learning challenged youth. CONCLUSIONS: Our results suggest that in typically developing youth, brain myelination contributes to individual differences in basic math achievement. In contrast, youth with learning challenges appear to have less capacity to leverage myelin to improve math achievement.